Heating up IDH-mutant gliomas - Platten, Michael; Bunse, Lukas (The New England journal of medicine, 2024)
A recent study unpicks a key immune-mediated mechanism of mutant IDH-blocking drugs such as vorasidenib in the treatment of IDH-mutant glioma.